The strategy of implementing Eurocode 2 in Malaysia - Ng, Ming Kwong (2007)
Code of practice is a document that is written to help engineers in designing. In Malaysia, the British Standard (BS) is the main source of structural design code. Start from 2010, BS 8110, the design code for the structural use of concrete, will be withdrawn to give way for the full implementation of Eurocodes in the United Kingdom (UK). Following the move, since 2001 The Institution of Engineers Malaysia (IEM) has issued Position Paper on Concrete Codes of Practice in Local Construction Industry After 2008. This position paper recommended Malaysia to adopt Eurocode 2 after year 2008. These changes have wide implication towards Malaysia construction industry especially on structural design of concrete but there are limited actions taken to prepare for the transition in this country. The study is carried out with the aim of identifying the strategy of implementing Eurocode 2. The method that are used this study are through literature reviews, questionnaire surveys and performing structured interview. Based on the finding, majorities of the construction professionals are aware of the impending changes of BS 8110 to Eurocode 2. However more efforts have to be taken to prepare themselves toward the challenges ahead. Seven strategies have also been identified for successful implementation of Eurocode 2 in Malaysia. These strategies cover various aspects such as the acceptance of Eurocode 2 by the authority, awareness campaign, allowance of transition period, education and training, research and development, funding and determine the leader in implementing Eurocode 2.